STAGES OF DEVELOPMENT OF THE CONSTITUTIONAL GUARANTEES OF THE RIGHT TO PRIVACY IN UZBEKISTAN. - Madiev Fakhriddin (Scholar Express Journals, 2023)
In this article the main directions of the impact of digitalization of society on the development of constitutional law are analyzed. It consists of a comprehensive analysis of stages of development of the constitutional guarantees of the right to privacy in Uzbekistan, as well as an analysis of the legal basis and specific aspects of the legal regulation of digitization in foreign countries, and to present proposals for improving the legislation of Uzbekistan on privacy
Keywords: digitization; privacy; personal data